Pengaruh Metode Outdoor Study Terhadap Keterampilan Menulis Teks Puisi Siswa Kelas X SMA Negeri 4 Binjai - Tresia Anggraini Malau; Wisman Hadi (Institut Nalanda, 2023)
This study aims to (1) analyze the poetry writing skills of class X students of SMA Negeri 4 Binjai before using the outdoor study method; (2) Analyzing the skills of writing poetry texts for class X students of SMA Negeri 4 Binjai after using the outdoor study method; (3) to analyze the effect of the outdoor study method on the skills of writing poetry texts for class X students of SMA Negeri 4 Binjai. The method used in this research is an experimental method with a one-group pre-test post-test design. The data analysis technique used in this research is quantitative data by testing the analysis requirements, homogeneity test, homogeneity test and hypothesis testing. The results showed that the average value of the students' poetry writing skills before using the outdoor study method was 54.55. The average score obtained by students after using the outdoor study method is 82.64% and is classified as good. Based on the results of the t test that has been carried out, it is obtained at a significant level a = 0.05, the ttable value is 2.03 and the result is tcount = 11.37. Then tcount ˃ ttable is 11.37 > 2.03, so that ho (null hypothesis) is rejected and ha (alternative hypothesis) is accepted. Overall, it can be concluded that teaching using the outdoor study method has a positive effect on the results of the skills of writing poetry texts for class X students of SMA Negeri 4 Binjai.